Insight into digital finance and fintech: A bibliometric and content analysis - Zou, Zongsen; Liu, Xindi; Wang, Meng; Yang, Xinze (Technology in society, 2023)
As an emerging financial service model, digital finance has gained tremendous popularity among providers and users. This paper explores the development of digital finance literature over the period 2006–2022, using a sample including 1191 documents from Web of Science (WoS) and Scopus databases. We adopt a hybrid approach combining the bibliometric method and content analysis. Fundamentally, using the bibliometric method, we have offered critical knowledge and information regarding the document types, number of annual publications, subject areas, the most prolific countries/institutions/journals/authors, and citation and co-citation network of authors/journals. Further, using the content method to classify, analyze, and summarize all the relevant documents, we have identified and delineated four thematic streams that dominate the research domain: applications and governance, critical underpinning technologies, digital financial services, and their effect on enterprises. Finally, detailed discussions regarding theoretical and practical implications and future research directions are presented to highlight the research objective of this paper. •Bibliometric and content analyses are performed to explore the development of digital finance and fintech research.•Prolific countries/institutions/journals/authors are identified through bibliometric analysis.•Hotspots are identified through density, theme, and content analyses.•We provide ideas to process substantial literature data from multiple sources.•The findings shed some light on researchers, policymakers, and practitioners.